ROLE OF AUTOLOGOUS NANOFAT GRAFTING IN THE TREATMENT OF POST ACNE AND POST BURN SCARRING OF THE FACE - Firdous Khan; Muhammad Kashif; Muhammad Shadman (Journal of Ayub Medical College Abbottabad, 2024)
Background: Post acne and post burn facial scarring are more common in young generation leading to disfigurement and unpleasing result. These scars have major aesthetic, functional, and social effects on the affected person. Aim of the study was to establish the role of Autologous Nanofat grafting in treating post acne & post burn facial scarring in terms of pleasing aesthetic appearance of face & patient satisfaction. Methods: A total no. of 24 patients with mean age of 23 years was enrolled in the study. Thirteen patients were of post acne face scarring and 11 patients were suffering from post-burn face scarring. There were 10 male and 14 female patients. All patients were treated with Nanofat grafting with an average of 3 sessions at an interval of 4-6 weeks. The results were assessed after 6 months from the last session by comparison of pre procedure & post procedure pictures and patient satisfaction. Results: Scars started improving after first session of Nanofat grafting and significant improvement in the scars was noted after 3rd session in terms of pigmentation, scar thickness and softness. Overall appearances of the scar were aesthetically improved a lot with a higher patient satisfaction rate. Conclusion: Autologous Nanofat grafting is a potential effective treatment modality for post-acne and post burn facial scarring with a good aesthetic outcome and higher patient satisfaction rate.